Upaya Pelestarian lingkungan dengan Mengangkat Budaya dan Kearifan Lokal dalam Sistem Konservasi Bukit, Tanah, Air di Wilayah Kalimantan Barat - Genopepa Sedia (Universitas Kapuas Sintang, 2023)
Communities have equal and broad rights and opportunities to play an active role in environmental protection and management and conservation of water, soil and biodiversity in Indonesia.Raising religious values and local wisdom in soil and water conservation, Humans are the main factor causing a lot of environmental damage related to water and soil resources such as river and reservoir sedimentation, soil pollution, and so on. Management and preservation of natural resources and the environment, including soil and water conservation, is an important issue because these issues threaten the survival of humans and other living things. So in conclusion the role of the community is to develop and maintain culture and local wisdom in the context of preserving environmental functions. Various local wisdom practices and ancestral cultures that are still maintained by the people of Indonesia can be one of the strategies for environmental protection and management. Preservation of local wisdom values and religious teachings related to the protection of natural resources and the environment is a form of conservation traditionally carried out by the community.